The Catalogs of Vices and Virtues in the Pauline Literature - Padilla, José David (Advances in Social Sciences Research Journal, 2021)
It was common to find in the writings of the different Greco-Roman philosophical schools of the first century certain catalogs of two or more vices and virtues. They were used to teach that a virtuous life ensured well-being and health while encouraging their disciples to abandon their vicious life leading to ruin. These catalogs influenced the composition of moral catalogs in the New Testament, especially in the letters written or attributed to Paul. Their catalogs were used as a rhetorical tool where the moral teachings of Christianity were developed and taught. According to the divine plan in Christ Jesus, good acts or virtues were considered divinely inspired because they helped the growth of the human person. On the other hand, bad actions or vices were seen as unworthy or sinful because they go against God’s plan and as a sign of those who will not inherit the kingdom of God. Thus, the catalogs of vices and virtues invited conversion and invited us to wait for the day when God will make all evil and corruption disappear from the world when love (agape), the Christian virtue per excellence, would be the norm for all.